Building Dual Earner Family Resilience through Self-Efficacy in Social Revolution 5.0 - Adelia Azhari Putri; Netty Herawati (Journal of Islamic Psychology and Behavioral Sciences, 2026)
The challenges posed by the Social Revolution 5.0 are becoming increasingly complex, particularly in terms of economic demands and roles. Economic development is driven by rapid technological advancements, meaning that working families must have the self-confidence to fulfill their roles both at work and as good family members so that the family can survive. The purpose of this study is to examine the role of self-efficacy in building family resilience among dual-earner families in the 5.0 era. The population and sample for this study consisted of 100 individuals serving as husbands or wives in dual-earner families. This study employed a quantitative method using a correlational approach with product-moment correlation analysis. The results indicate that self-efficacy has a positive and significant relationship with building family resilience, with a correlation coefficient of 0.524 (p > 0.05). Therefore, the higher the level of self-efficacy, the higher the resilience of dual-earner families. Future researchers may explore factors influencing family resilience, such as the impact of gender roles, marital satisfaction, child-rearing practices, and emotional regulation within the family.